2015
DOI: 10.1002/pi.4905
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the lignin based synthesis of flexible polyurethane foams employing reactive liquefying agents

Abstract: The present work is focused on the optimization of a green process based on the employment of by-products obtained from wood treatments as raw materials for producing flexible polyurethane foams. More specifically, lignin was employed in flexible polyurethane foams in order to partially replace the usual fossil polyols; therefore glycerol (GLY) and glycerin polyglycidyl ether (EJ 300) were used as the polyol fraction for lignin liquefaction. Polypropylene glycol triol was used as a chain extender in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…In a previous work, A. donax hydrolysis residue was characterized and compared with ProtoBind 1000, a technical soda lignin used for the synthesis of polyurethane foams (Bernardini et al 2015a, b). It was found that A. donax hydrolysis residue had a brown coal lignite-like elemental composition (C: 63.6%, H: 4.3%, N: 0.7%, O: 31.4%).…”
Section: Arundo Donax L Hydrolysis Residue and Protobind 1000 Soda Lmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous work, A. donax hydrolysis residue was characterized and compared with ProtoBind 1000, a technical soda lignin used for the synthesis of polyurethane foams (Bernardini et al 2015a, b). It was found that A. donax hydrolysis residue had a brown coal lignite-like elemental composition (C: 63.6%, H: 4.3%, N: 0.7%, O: 31.4%).…”
Section: Arundo Donax L Hydrolysis Residue and Protobind 1000 Soda Lmentioning
confidence: 99%
“…PEG 400 was replaced with the EJ 300, a mixture of glycerol polyglycidyl ethers. The amount of EJ 300 was altered and tested, creating two mixtures named ARF and ARJ using the reported procedure (Bernardini et al 2015a). By lowering the isocyanate index, the lignin content in the final foam was maximized, and foams with stable structures were obtained.…”
Section: Production Of Arundo Donax L Hydrolysis Residue Based -Polymentioning
confidence: 99%
See 2 more Smart Citations
“…Lignin and its derivatives were employed as renewable resources for flexible (Cinelli et al 2013;Bernardini et al 2015) and rigid (Xue et al 2015) PUR foams. An extensive up-to-date discussion of the pathways for lignin conversion into polyols can be found in the review papers by Matsushita (2015) and Mahmood et al (2016).…”
Section: Introductionmentioning
confidence: 99%